The Role of Intention In Mediating the Effects of Perceptions of Tax Fairness and the Image of the Directorate General of Taxes on Taxpayer Compliance - Hanim Batubara, Sarah; Farida Ferine, Kiki; Erwansyah (International Conference Epicentrum of Economic Global Framework, 2026)
This study aims to analyze the role of tax payment intention in mediating the influence of perceptions of tax fairness and the image of the Directorate General of Taxes on taxpayer compliance at the Lubuk Pakam Primary Tax Office. This study uses a quantitative approach with a survey method. The study population consisted of active individual taxpayers in Hamparan Perak Village, Kelambir Village, and Kelambir Lima Kebun Village, Deli Serdang Regency. The sample size was 388 respondents, determined using the Slovin formula with a 5% margin of error. Primary data were collected through a Likert-scale questionnaire. Data analysis employed Partial Least Squares Structural Equation Modeling using SmartPLS 3.0. The results indicate that perceptions of tax fairness have a positive and significant effect on tax payment intention and taxpayer compliance. The image of the Directorate General of Taxes (DJP) also has a positive and significant effect on tax payment intention and taxpayer compliance. Furthermore, the intention to pay taxes has a positive and significant effect on taxpayer compliance. Indirect testing results indicate that the intention to pay taxes mediates the effects of perceptions of tax fairness and the image of the DGT on taxpayer compliance. The R-squared value indicates that the model explains 23% of the variance in tax payment intention and 40.8% of the variance in taxpayer compliance. These findings confirm that taxpayer compliance is determined not only by administrative regulations but also by perceptions of fairness, institutional image, and taxpayers’ internal intentions.